An Exploration of the Influence of TikTok Application and Online Game Addiction on Grade X Students' Understanding of Islamic Religious Education - Sehat, Sumurubu; Satir, Muhammad; Khatipah, Khatipah; Umrah, St. (South Sulawesi Education Development (SSED), 2025)
This study aims to examine the impact of addiction to TikTok and online games on the understanding of Islamic Religious Education among 10th-grade students at SMA Negeri 1 Sorong City. Using a descriptive qualitative approach, data were collected through in-depth interviews with PAI teachers and guidance counselors, as well as classroom observations. The findings reveal that excessive use of TikTok and online games significantly reduces students’ concentration, time management skills, and ability to comprehend and internalize Islamic values. Students often show procrastination, decreased discipline, and lower motivation in learning PAI. These behaviors not only affect their academic performance but also their religious attitudes. The study suggests implementing digital literacy education, strict regulations on gadget usage, and active collaboration between schools and parents to minimize negative impacts while promoting responsible and balanced use of technology.